Need Analysis of Interactive Electronic Student Worksheets on Dynamic Fluids Based on Dual Space Inquiry to Stimulate Students’ Science Process Skills - Winda Rudespika; Fuja Novitra; Akmam Akmam; Selma Riyasni (Universitas Negeri Padang, 2026)
This research is motivated by the urgency of the Science–A Process Approach (SAPA), which emphasizes the importance of science process skills in physics learning. However, classroom practices still show low student engagement in scientific activities and are dominated by conventional teaching materials. This research aims to analyze the need for developing interactive Electronic Student Worksheets based on the Dual Space Inquiry approach to stimulate students’ science process skills on dynamic fluid topics. The research uses an Educational Design Research approach with the Plomp model, focusing on the preliminary research phase through needs analysis. Data were collected through observations, interviews, and questionnaires involving students and teachers and analyzed descriptively. The results indicate that students’ science process skills are generally low, especially in classifying, inferring, predicting, and communicating. In addition, teaching materials have not optimally integrated science process skills and show minimal use of digital technology, while students have a high demand for interactive digital learning materials. These findings reveal a gap between SAPA-based learning expectations and classroom practices. Therefore, the development of interactive Electronic Student Worksheets based on Dual Space Inquiry is recommended to support inquiry-based learning and improve students’ science process skills.